Analysis of the Competitiveness Tourism Industries Increasing the Local Economy (The Comparative Study Analysis of the Competitiveness Tourism between Surakarta and Yogyakarta) - Rina Trisnawati; Wiyadi Wiyadi; Edy Priyono (Economic Journal of Emerging Markets, 2008)
The purpose of this study are measuring tourism competitiveness in Surakarta region and determining the contribution of tourism for economic region. These cases are compared with Yogyakarta region as benchmark region for tourism in Indonesia. The study is important because it contributes to PAD (Pendapatan Asli Daerah) and gives impact on related industries such as: travel agent, hotel, restaurant, and small industries. The analysis of this study used Competitiveness Monitor (CM) that is the popular measurement to determine tourism competitiveness. It was used more than 200 countries and it is developed by World Travel and Tourism Council (WWTC). The indicators of CM are Human Tourism Indicator, Price Competitiveness Indicator, Infrastructure Development Indicator, Environment indicator, Technology Advancement Indicator, Human Resources Indicator, Openess Indicator, dan Social Development Indicator. From these indicators, we measure tourism competitiveness index and classify the region in green, grey or red area of tourism competitiveness. The result of analysis indicates the Surakarta region is classified in grey area region of tourism competitiveness. The result also indicates the position of tourism competitiveness of Surakarta region with Yogyakarta region. The government has to develop the tourism sector by analysis the indicators which determine the tourism competitiveness because the tourism sector gives the added revenues for the region. It is very important, whichever Adisumarmo airport (Surakarta) is one of the international airport in Indonesia. Keywords: tourism, competitiveness, index, competitiveness monitor, tourism competitiveness index, local economy